2021
DOI: 10.1038/s41598-021-88518-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Let-7 targets AMPK and impairs hepatic lipid metabolism in offspring of maternal obese pregnancies

Abstract: Nutritional status during gestation may lead to a phenomenon known as metabolic programming, which can be triggered by epigenetic mechanisms. The Let-7 family of microRNAs were one of the first to be discovered, and are closely related to metabolic processes. Bioinformatic analysis revealed that Prkaa2, the gene that encodes AMPK α2, is a predicted target of Let-7. Here we aimed to investigate whether Let-7 has a role in AMPKα2 levels in the NAFLD development in the offspring programmed by maternal obesity. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Suppression of G-subunit gene expression can suppress the activity of the AMPK complex. In the work of Simino et al (2021) , Prkaa2 (AMPKα2) was shown to be a direct let-7 target in the liver in a steatosis model ( Simino et al, 2021 ). In general, a decrease in the expression of AMPK complex genes by RNA-dependent epigenetic regulation indicates dysfunction of the complex, consistent with data from other researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of G-subunit gene expression can suppress the activity of the AMPK complex. In the work of Simino et al (2021) , Prkaa2 (AMPKα2) was shown to be a direct let-7 target in the liver in a steatosis model ( Simino et al, 2021 ). In general, a decrease in the expression of AMPK complex genes by RNA-dependent epigenetic regulation indicates dysfunction of the complex, consistent with data from other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of G-subunit gene expression can suppress the activity of the AMPK complex. In the work of Simino et al (2021), Prkaa2 (AMPKα2) was shown to be a direct let-7 target in the liver in a steatosis model (Simino et al, 2021).…”
Section: Differentially Expressed Mirnas Alter Energy Balance In the Liver By Targeting Genes Of The Ampk Complexmentioning
confidence: 99%
“…Recently, there has been evidence that the expression of Let-7 is linked to glucose metabolism and insulin levels during pregnancy. Furthermore, Let-7 -mediated AMPK contributes to liver metabolism [ 151 ]. Additionally, Zhong et al revealed that one diabetes-related drug, metformin, increases AMPL activity and Let-7 to regulate gene methylation in ARK2 and MCF-7 cells [ 152 ].…”
Section: Possible Connections Between Let-7 -Mediated Glycolysis and Autophagy In Cancer Progressionmentioning
confidence: 99%
“…NAFLD is defined as an ectopic lipid accumulation within the hepatocytes up to 5% in the absence of drugs or alcohol consumption ( Lindenmeyer and McCullough, 2018 ), which can progress to stages with associated inflammation and fibrosis, fatally causing liver failure ( Koppe, 2014 ; Bellentani and Med Stefano Bellentani, 2017 ). Recent studies have demonstrated that NAFLD development can be triggered during fetal and early stages of life, as a consequence of exposure to a maternal obesogenic environment, such as a high-fat diet (HFD) consumption ( Hoover et al, 1987 ; Fernandez-Twinn et al, 2015 ; Simino et al, 2021 ). In addition, the HFD consumption by dams predisposes offspring to higher body weight and adiposity, dyslipidemia, and insulin resistance at different stages of life ( Melo et al, 2014 ; Fante et al, 2016 ; Lemes et al, 2018 ; Castro-Rodríguez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the HFD consumption by dams predisposes offspring to higher body weight and adiposity, dyslipidemia, and insulin resistance at different stages of life ( Melo et al, 2014 ; Fante et al, 2016 ; Lemes et al, 2018 ; Castro-Rodríguez et al, 2021 ). The development of these metabolic abnormalities in the offspring, as well as NAFLD, has shown to be under epigenetic control ( Benatti et al, 2014 ; Fernandez-Twinn et al, 2015 ; Bianco-Miotto et al, 2017 ; Simino et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%